The association between chronic kidney disease, waist circumference and body mass index: A case-control study from a tertiary hospital of West Bengal, India - Anirban Ghosh; Somak Kumar Das (Wolters Kluwer Medknow Publications, 2020)
Introduction: In this hospital-based study, we investigated the association between chronic kidney disease (CKD) and two globally accepted obesity parameters - waist circumference (WC) and body mass index (BMI). Aims: To investigate the association between CKD with BMI and WC. Materials and Methods: We included 416 consecutive CKD patients (age >20 years, calculated glomerular filtration rate <60 ml/min/1.73 m2) as the case group and 408 consecutive age- and sex-matched non-CKD patients as the control group for our study. after obtaining consent, all groups were tested for WC and BMI. Results: Of 416 cases, the prevalence of high WC according to the International Diabetes Federation (IDF) criteria was 37.5% and of obesity according to the Indian BMI scale was 38.46%. When compared with the control group, we found that WC (p < 0.0001, odds ratio [OR] 2.182, 95% confidence interval [CI] 1.099-1.852) and BMI (p = 0.006, OR 3.125, 95% CI 1.625-3.125) were significantly high in the CKD group. Conclusion: The parameters of obesity were found to be significantly associated with the non-edematous CKD group.